THE SETTLEMENT OF ADOPTED CHILDREN STATUS REGARDING THE INHERITANCE OF ADOPTION PARENTS IN TORAJA COMMUNITIES - Poespasari, Ellyne Dwi; Usanti, Trisadini Prasastinah; Soelistyowati (jfpublisher, 2023)
The child adoption in Toraja community is valid when it is conducted with traditional ceremony. However, the adoption of children that declared with traditional ceremonies still does not fully meet the requirements in written law which can lead to the legitimacy of adopted child position as the heir of his adoptive parents. The settlement of disputes over the inheritance distribution of adopted children can be resolved through the deliberations of relatives and customary heads. However, in its development, the Toraja community began to resolve these disputes through the courts, because it was considered more capable of providing justice and legal certainty. This legal research is empirical research (socio-legal research) that can be classified into analytical descriptive research. The data used is primary data, which is obtained from observation, interviews with respondents and informants while secondary data is in the form of judge's decisions and related legal theories.